If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6z + 8 + -4 = 25 Reorder the terms: 8 + -4 + -6z = 25 Combine like terms: 8 + -4 = 4 4 + -6z = 25 Solving 4 + -6z = 25 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -6z = 25 + -4 Combine like terms: 4 + -4 = 0 0 + -6z = 25 + -4 -6z = 25 + -4 Combine like terms: 25 + -4 = 21 -6z = 21 Divide each side by '-6'. z = -3.5 Simplifying z = -3.5
| 4.2=2.7+h | | 8x-11+x=3+4x-19 | | 5y-1+21=6y+20-3y | | 3x-18=2x+10 | | 4x+3y=292 | | 9t-5=4t+10 | | h=16t^2+14 | | -21-9h=-3(4h+5) | | [7+(-3)]+(-5)=7+[(-3)+(-5)] | | 30-7m+10-3m= | | 2x+2*2x+7=2x+7 | | -21-9h= | | (X+28)=(3x+14) | | 260-64-9= | | (2/7)÷N=(5/7) | | 9.8k+3.7=-0.22 | | a^2-4a+4-b^2= | | y=3e^5x | | 3/4(x-6)=2/8(x+2) | | y^2-16x-64=0 | | 38*x^3+19x^2-158=0 | | R=D-TforD | | .5x-2=.3x+1.2 | | -4c+3-6c=34 | | -x+4x=40 | | 2log(x-5)=6 | | Z/12=12/4 | | X/12=59/60 | | y=-3x^2-6(3)-5 | | 3/w=18/42 | | x^2+4m-12=0 | | N-3=20/8 |